Peningkatan Kualitas SDM dalam Menghadapi Transformasi Industri 4.0 di Yayasan Tajaul Karomatu Desa Situ Gadung Tangerang - Muhamad Guruh; Iman Syatoto; Hadyati Harras (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid development of Industry 4.0 has brought significant changes to various sectors, including education, requiring human resources (HR) to possess adequate skills and competencies to adapt effectively. This community service activity aimed to enhance the quality of human resources in facing the Industry 4.0 transformation at Yayasan Tajaul Karomatu, Situ Gadung, Tangerang. The activity was conducted from April 8–10, 2025, by a team of eight lecturers and students from Universitas Pamulang, targeting 24 participants consisting of students and teachers. The methods employed included material presentations, interactive discussions, and question-and-answer sessions to facilitate knowledge transfer and skill development. The PKM implementation was carried out in three stages: preparation, execution, and reporting. During the preparation stage, the team designed materials and coordinated with the foundation to arrange schedules and logistics. The execution stage involved delivering structured sessions that addressed Industry 4.0 concepts, required competencies, and practical strategies for adaptation. Finally, the reporting stage documented the outcomes, feedback, and recommendations for further improvement. The results indicated that participants gained increased awareness and understanding of Industry 4.0, developed critical thinking skills, and expressed confidence in applying new knowledge in learning and teaching processes. This PKM activity contributed to strengthening the capacity of the foundation’s human resources to respond to technological transformation challenges effectively.